2020
DOI: 10.1111/irel.12249
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Between‐Plant and Within‐Plant Wage Dispersion: Evidence from Germany

Abstract: Using rich linked employer-employee data for (West) Germany between 1996 and 2014, we conduct a decomposition analysis based on recentered influence function (RIF) regressions to analyze the relative contributions of various plant and worker characteristics to the rise in German wage dispersion. Moreover, we separately investigate the sources of between-plant and within-plant wage dispersion. We find that industry effects and the collective bargaining regime contribute the most to rising wage inequality. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 60 publications
4
17
0
1
Order By: Relevance
“…8. This is in line with existing studies on the role of trade on wage inequality based on matched employer-employee data in individual countries, including Germany and Brazil (Baumgarten et al, 2016;Helpman et al, 2017). 9.…”
Section: The Role Of Public Policies and Institutionssupporting
confidence: 90%
See 1 more Smart Citation
“…8. This is in line with existing studies on the role of trade on wage inequality based on matched employer-employee data in individual countries, including Germany and Brazil (Baumgarten et al, 2016;Helpman et al, 2017). 9.…”
Section: The Role Of Public Policies and Institutionssupporting
confidence: 90%
“…the measure of wage dispersion used in the aggregate analysis. This is consistent with a large body of evidence based on linked employer-employee data suggesting that between-firm wage divergence is a key explanation of wage divergence across individual workers, including for Brazil (Helpman et al, 2017), Denmark (Bagger et al, 2013), Germany (Baumgarten et al, 2016;Card et al,2013;Goldschmidt and Schmieder, 2015), Italy (Card et al, 2014), Portugal (Card et al, 2016), Sweden (Skans et al, 2009), United Kingdom (Faggio et al, 2010) and the United States (Dunne et al, 2004;Barth et al, 2016;Song et al, 2015).…”
Section: The Facts: Aggregate and Disaggregated Perspectivessupporting
confidence: 87%
“…On average, plants covered by a collective agreement have a higher value added per worker (Mueller 2011) and also pay higher wages (Gürtzgen 2009). Furthermore, studies by Dustmann, Ludsteck, and Schönberg (2009), Biewen and Seckler (2019), and Baumgarten, Felbermayr, and Lehwald (2020) have found that declining collective bargaining coverage can account for a substantial part of the rise in German wage inequality. Yet, evidence on these links between collective bargaining coverage and wages does not necessarily carry over to plant wage premia.…”
Section: Institutional Setting and Some Hypothesesmentioning
confidence: 99%
“…Die Ungleichheit scheint bei seit 2011 real ansteigenden Löhnen weitestgehend stabil zu sein. In den Analysen von Baumgarten et al (2020) und Möller (2016) sind es die Unterschiede zwischen den Firmen, welche auf den Verlauf der Ungleichheit -Anstieg und anschließende Stagnation -den stärksten Einfluss haben.…”
Section: Literatur Zur Entwicklung Der Lohnungleichheitunclassified